The influence of sex hormones on ocular blood flow in women - TOKER, AYŞE EBRU; ŞAHİN, ÖZLEM (WILEY, 2003)
Purpose: To investigate the influence of sex hormones on ocular haemodynamics, blood flow velocities in the ophthalmic and central retinal arteries and serum levels of sex hormones were measured in pre- and postmenopausal women. Methods: Colour Doppler imaging (CDI) was used to determine the flow velocities (peak systolic velocity [PSV] and end-diastolic velocity [EDV]) and the resistive index (RI) in the ophthalmic and central retinal arteries in 22 premenopausal and 32 postmenopausal women, who had never received hormone replacement therapy. Serum levels were measured for oestradiol, free testosterone and follicle-stimulating hormone. The CDI parameters were compared between the two groups and the influence of serum levels of oestradiol and testosterone on blood flow velocities and the resistive indices were analysed. Results: After correcting for age and mean arterial blood pressure, an analysis of covariance disclosed a significantly lower EDV (p = 0.02) and a significantly higher RI (p = 0.01) in the central retinal artery of postmenopausal women compared with premenopausal women. Partial correlation analysis, controlling for age, revealed significant correlations between the CDI parameters and serum levels of oestradiol and testosterone. For premenopausal women, PSV (r = 0.58, p = 0.04) and EDV (r = 0.73, p = 0.006) in the ophthalmic artery correlated positively with serum oestradiol levels. The RI in the central retinal artery decreased with increasing oestradiol levels in both groups (premenopausal r = - 0.40, p = 0.04; postmenopausal r = - 0.32, p = 0.05). Peak systolic velocity in the central retinal artery correlated negatively (r = - 0.49, p = 0.04), whereas the RI correlated positively (r = 0.53, p = 0.02) with testosterone levels in the premenopausal group. Postmenopausal women with higher testosterone levels had lower EDV (r = - 0.53, p = 0.007) in the central retinal artery and higher RI in both vessels (ophthalmic artery r = 0.48, p = 0.01; central retinal artery r = 0.61, p = 0.002). Conclusion: Our data provide evidence of a relationship between serum sex hormone levels and blood flow velocities and resistive indices in retrobulbar arteries. Oestradiol appears to have beneficial effects on ocular haemodynamics, whereas testosterone may act as an antagonistic to the effects of oestrogen.
Keywords: oestradiol; testosterone; menopause; ocular blood flow; colour Doppler imaging; REPLACEMENT THERAPY; POSTMENOPAUSAL WOMEN; CEREBRAL-ARTERIES; PULSATILITY INDEX; NITRIC-OXIDE; ESTROGEN; TESTOSTERONE; AGE; PROSTACYCLIN; ESTRADIOL